2018
DOI: 10.23887/ijssb.v2i2.13987
|View full text |Cite
|
Sign up to set email alerts
|

Measuring How Destination Image and Perceive Value Affect Customers’ Satisfaction for Ecotourism

Abstract: This study purpose is to determine the effect of destination image and perceived value on the satisfaction’s level of the tourists who visit ecotourism attractions. There are two studies conducted in this research, the first is to validate the effect of destination image to the customers' satisfaction level and also to see the dominant effect of each indicator from the destination image to Customer Satisfaction level. Subsequent study validates the effect of Perceived Value on the customers' satisfaction level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
(10 reference statements)
4
1
0
Order By: Relevance
“…Regarding the perceived value and its relation to general satisfaction, our results have found that all the dimensions of the perceived value were significantly and positively related to general satisfaction. Similar results were found in other studies (Carvache-Franco et al, 2019;Jaya, 2018;Lee et al, 2007;Lee et al, 2010;Peña et al, 2012;Sun et al, 2013), which indicates that all dimensions of perceived value are related to overall satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Regarding the perceived value and its relation to general satisfaction, our results have found that all the dimensions of the perceived value were significantly and positively related to general satisfaction. Similar results were found in other studies (Carvache-Franco et al, 2019;Jaya, 2018;Lee et al, 2007;Lee et al, 2010;Peña et al, 2012;Sun et al, 2013), which indicates that all dimensions of perceived value are related to overall satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, Kim and Thapa (2018) established the emotional and social dimensions in satisfaction, similar to our second motivation, "emotional value." Also, for Jaya (2018), the perceived values that should be the material of the evaluation were the functional and the emotional values, comparable to our economic-functional and emotional results. For Carvache-Franco et al (2019), functional and emotional values were linked to satisfaction and loyalty, results that are closely related to ours (economic-functional and emotional values).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations